1995
DOI: 10.1021/j100044a023
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Stability of Zeolite Offretite under Si4+/(Al3+, M+) Substitution (M = Na, K): A First Principles Molecular Dynamics Study

Abstract: A local density functional study of the structure and energetics of offretite, with a Si4+ ion substituted by (A13+, M+) (M = Na, K), is presented. The calculations have been performed within the framework of the first principles molecular dynamics method using a periodically repeated unit cell with 55 atoms. It is found that the preferred site for K+ cations lies inside the cancrinite cage, in agreement with experiment. This site is related to A1 substituting a Si atom at a TI site, which is one of the two in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
0
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 8 publications
4
23
0
1
Order By: Relevance
“…14 In turn, the extra-framework cations also significantly influence the energetics and structural stability of the zeolite frameworks. 15,16 The cations may also act as precursors to obtain new zeolite frameworks. 17 Therefore, understanding the underlying thermodynamic properties defining the structure, stability, phase evolution and cation-water-framework interactions is fundamentally important for the synthesis and industrial development of zeolites.…”
Section: Introductionmentioning
confidence: 99%
“…14 In turn, the extra-framework cations also significantly influence the energetics and structural stability of the zeolite frameworks. 15,16 The cations may also act as precursors to obtain new zeolite frameworks. 17 Therefore, understanding the underlying thermodynamic properties defining the structure, stability, phase evolution and cation-water-framework interactions is fundamentally important for the synthesis and industrial development of zeolites.…”
Section: Introductionmentioning
confidence: 99%
“…During the last decade, the main effort has been devoted to H-zeolites, mainly due to their widespread applications in acid catalysis. [5][6][7] Only recently have some dynamical studies of Na and Ca A-zeolite, [8][9][10] Na Y-zeolite, 11 and Na and K offretite 12 proposed detailed structures including cation positions. In recent papers, we have shown that the nature of the cation and its location in the framework are essential factors for N 2 and O 2 adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…[89][90][91][92][93][94]). In the mid-1990s, she investigated the structural parameters and the energetic of offretite [89][90][91] using the local density approximation within the framework of Car-Parrinello method [65]. In the meantime, the substitution of silicon by aluminum at different tetrahedral sites of zeolite-b and the influence of the counter ion were performed for the first time at a correlated level of theory [92].…”
Section: Applications To Zeolites: a Tribute To Dr Annick Goursotmentioning
confidence: 99%